2005
DOI: 10.1021/ma0478207
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Segmented Copoly(ether urea)s with Uniform Hard Segments

Abstract: Employing protective group strategy and novel isocyanate chemistry, segmented copoly(ether urea)s with uniform hard segments were prepared. Amine-terminated poly(tetrahydrofuran) served as the soft segment of these polymers. The size of the hard segments and the number of urea groups it contains were varied systematically, and their influence on the properties was investigated. The strength of hydrogen bonding between the urea groups in monodisperse hard segments containing exactly 1 to exactly 4 urea groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(123 citation statements)
references
References 62 publications
6
117
0
Order By: Relevance
“…As summarized in Table 2, all ionogels exhibit similar N-H stretch bands ranging from 3316 to 3329 cm −1 and amide-I bands around 1616 cm −1 , indicating the existence of rather strong intermolecular hydrogen bonding between the urea groups even in the ionic liquid. 26 This is in agreement with earlier studies of this Scheme 1 Chemical structures of macrocycle-functionalized gelator 1 and the ionic liquids IL-1 to IL-4 under study here. gelator in acetonitrile and other organic solvents that showed that PF 6 − does not interfere with these hydrogen bonding interactions.…”
Section: Ft-ir Characterization and Gel Morphologysupporting
confidence: 91%
See 1 more Smart Citation
“…As summarized in Table 2, all ionogels exhibit similar N-H stretch bands ranging from 3316 to 3329 cm −1 and amide-I bands around 1616 cm −1 , indicating the existence of rather strong intermolecular hydrogen bonding between the urea groups even in the ionic liquid. 26 This is in agreement with earlier studies of this Scheme 1 Chemical structures of macrocycle-functionalized gelator 1 and the ionic liquids IL-1 to IL-4 under study here. gelator in acetonitrile and other organic solvents that showed that PF 6 − does not interfere with these hydrogen bonding interactions.…”
Section: Ft-ir Characterization and Gel Morphologysupporting
confidence: 91%
“…For the imidazolium-cation-based ionic liquids, all K a values are below 1000 M −1 and close to those measured for the same host-guest complex in acetone (615 M −1 ). 26 In IL-4, the K a value turns out to be significantly higher with 5300 M −1 . This indicates the nature of the cation to play a pivotal role, while the anion has only minor effects on pseudorotaxane formation.…”
Section: Gel-sol Transitions Induced By Molecular Recognitionmentioning
confidence: 88%
“…[1][2][3][4][5][6][7][8] However, the polyurethanes with monodisperse HSs are difficult to prepare and they lose their mono-disperse distribution upon melting due to transurethane reactions. [4] Mono-disperse HS shows an enhanced thermal stability when constituted of diurethanediurea-diamide since trans-reactions do not change the distribution of these HSs.…”
Section: Introductionmentioning
confidence: 99%
“…Building on Lehn and coworkers initial work on hydrogen-bonded monomer units [16], and the studies of Griffin and coworkers of main-chain supramolecular polymers based on simple hydrogen bonding motifs [17,18], the Meijer group was the first to demonstrate supramolecular systems which exhibited polymer-like properties [19][20][21][22][23][24]. The latter were accountedfor by the comparably high dimerization constant of the ureidopyrimidinone (UPy) motif employed, the use of telechelic building blocks, and phase segregation effects.…”
Section: Introductionmentioning
confidence: 99%